Penerapan pelajaran bahasa Arab dalam pembiasaan membaca Al-Qur'an - Muhammad Rifqi (Studi Administrasi Publik dan ilmu Komunikasi, 2024)
Dede Sobayar. 182100092. 2021. Application of Arabic Language Lessons in the Habit of Reading the Qur'an As Muslims, we are required to always read and study the Qur'an in accordance with the decision issued by the Minister of Religion of the Republic of Indonesia, which requires every Muslim to continue to improve their abilities and interest in reading the Koran. To achieve this goal, many Al-Qur'an study institutions have created various methods, one of which is by linking Arabic language lessons to the habit of reading the Al-Qur'an. Learning Arabic is one application in getting used to reading the Koran. By getting into the habit of reading the Qur'an through Arabic lessons, interest in reading and the ability to improve reading of the Qur'an, such as tajwid, makharijul letters, and others, will increase. The aim of this research is to get an overview of the application of Arabic language lessons in the habit of reading the Al-Qur'an. The research method used is descriptive, which can explain the topic to be studied. The results of this study show that Arabic plays an important role in reading the Koran. The background to this research is that there are still many children who lack focus and lack enthusiasm in implementing the Al-Qur'an reading habit program, and do not pay enough attention to and implement habituation programs both at school and at home. Therefore, the application of Arabic language lessons in the habit of reading the Al-Qur'an is able to increase students' reading interest, skills and fluency in reading the Al-Qur'an, both at school, home and in everyday life.